Green Tax Shocks and Economic Growth - Mohammed, Mikidadu (International Journal of Energy Economics and Policy, 2020)
The purpose of this paper is to examine the long-run relationship between green tax and economic growth. Specifically, it utilizes the sign-restrictions structural vector autoregressions to examine whether green tax is growth-enhancing or growth-inhibiting. Using data on the Danish economy for the period 1975-2017, the results reveal that green tax shocks trigger opposite movements in non-renewable and renewable energy consumption, and a mild transitory decrease in economic growth. The study also compares green tax shocks in the pre- and post-Carbon tax periods and finds that how the Danish economy experiences green tax shocks has not fundamentally changed since the introduction of Carbon tax in 1992. Taken together, the findings suggest that green tax is effective in increasing reliance on renewable energy while decreasing non-renewable energy consumption without seriously inhibiting economic growth. Keywords: green tax, carbon tax, economic growth, structural var JEL Classifications: E62; O44; Q43 DOI: https://doi.org/10.32479/ijeep.8660